2012
DOI: 10.1002/cbdv.201100386
|View full text |Cite
|
Sign up to set email alerts
|

microRNA Dysregulation in Prostate Cancer: Network Analysis Reveals Preferential Regulation of Highly Connected Nodes

Abstract: microRNAs (miRNAs) are small RNAs shown to contribute to a number of cellular processes including cell growth, differentiation, and apoptosis. MiRNAs regulate gene expression of their targets post-transcriptionally by binding to messenger RNA (mRNA), causing translational inhibition or mRNA degradation. Dysregulation of miRNA expression can promote cancer formation and progression. Research has largely focused on the function and expression of single miRNAs. However, complex physiological processes require the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 36 publications
(47 reference statements)
0
18
0
Order By: Relevance
“…Finally, we compared the FFLs reconstructed from pan-cancer and prostate cancer datasets and identified 2 TF-FFLs (Figure 3B) that appeared in both datasets. Interestingly, the miRNAs in these two FFLs, hsa-let-7a and hsa-let-7e, belong to the hsa-let-7 family that is related to prostate [35], breast [36], lung [37] cancers.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we compared the FFLs reconstructed from pan-cancer and prostate cancer datasets and identified 2 TF-FFLs (Figure 3B) that appeared in both datasets. Interestingly, the miRNAs in these two FFLs, hsa-let-7a and hsa-let-7e, belong to the hsa-let-7 family that is related to prostate [35], breast [36], lung [37] cancers.…”
Section: Resultsmentioning
confidence: 99%
“…microRNAs involved in prostate cancer progression preferentially target interactome hubs (Budd et al, 2012). microRNA networks obtained from 3,312 neoplastic and 1,107 nonmalignant human samples showed the dysregulation of hub microRNAs.…”
Section: Four Examples Of Network Description and Analysis In Drugmentioning
confidence: 99%
“…Network analysis have shown that genes that are subject to extensive miRNAs regulation, referred as to target hubs, are more likely to be biologically relevant (30,31). In addition, it has been shown that many TFs are among these target hubs and there is increasing evidence of reciprocal regulation between miRNAs and TFs as well as the existence of extensive coordination in the regulation of shared targets genes at the genome-scale level (32,33).…”
Section: Identification Of Mirnomes In Normal Thyroid and Ptc Unveilsmentioning
confidence: 99%